The Performance of Various Rear Facing Child Restraint Systems in a Frontal Crash - Sherwood, C. P. (Association for the Advancement of Automotive Medicine, 2004)
Current forward facing (FF) child restraint designs use LATCH and ISOFIX systems to couple the restraint to the vehicle. Rear facing (RF) child restraints, however, have multiple coupling methods that vary by manufacturer and country of origin. Sled tests were performed with the CRABI 12 month dummy in six different RF attachment conditions. The performance of the rear facing child restraints (restraint kinematics, head accelerations, and neck loads) was highly dependent on the coupling method used. The results were also compared to a FF LATCH restraint.